Identifying needs and problems in learning for children with autism spectrum disorder (ASD) from a technology perspective - Ishak, Norshahidatul Hasana; Mohamad, Siti Nurul Mahfuzah; Syamimi, Shamsuddin; Mohamad Lutfi, Dolhalit; Aliza, Alias; Sazilah, Salam (2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterised by difficulties in social communication and interaction and repetitive behaviours. No scientific study has yet been able to establish the exact cause of ASD. According to statistics, an increasing number of children are diagnosed with ASD each year. Education is important for children with ASD, just like other children. The teaching techniques adopted in special education may impact the learning ability of these children with ASD. Current teaching aids sometimes cannot effectively assist children with ASD in enhancing their cognitive ability. This preliminary study is aimed to help gather data to identify and analyse current issues in teaching and learning involving children with ASD. Surveys and interviews were conducted with experts, teachers, and parents through focus group discussions to investigate the current problem of ASD in children and the impact of using the robot as a technology to deliver learning sessions for improving cognitive ability. Results show that it was challenging for the children to give attention and focus during learning. Their cognitive ability is also low. Current teaching methods sometimes cannot make them happy and interested in learning. Hence, this research proposes robots as an assistive tool to overcome the problem of teaching and learning for children with ASD.